2015
DOI: 10.1519/jsc.0000000000001035
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Physical Training During Military Basic Training Period

Abstract: The goal for military basic training (BT) is to create a foundation for physical fitness and military skills of soldiers. Thereafter, more advanced military training can safely take place. Large differences in the initial physical performance of conscripts or recruits have led military units to develop more safe and effective training programs. The purpose of this review article was to describe the limiting factors of optimal physical training during the BT period. This review revealed that the high volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 22 publications
1
31
0
6
Order By: Relevance
“…Military training and operations consist of tasks that can be attained through combined strength and endurance training. 28 Therefore, it can be concluded that combined strength and endurance training is the foundation of soldiers' physical performance. 29 The combined training may well induce positive training adaptations both in aerobic fitness and muscle strength capabilities in poorly-conditioned, overweight and inactive individuals.…”
Section: Combined Strength and Endurance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Military training and operations consist of tasks that can be attained through combined strength and endurance training. 28 Therefore, it can be concluded that combined strength and endurance training is the foundation of soldiers' physical performance. 29 The combined training may well induce positive training adaptations both in aerobic fitness and muscle strength capabilities in poorly-conditioned, overweight and inactive individuals.…”
Section: Combined Strength and Endurance Trainingmentioning
confidence: 99%
“…29 The combined training may well induce positive training adaptations both in aerobic fitness and muscle strength capabilities in poorly-conditioned, overweight and inactive individuals. 28 However, training adaptations are being compromised in more fit and active individuals. This phenomenon is called interference effect, which was first established by Hickson 30 The interference on optimal strength training adaptations may be caused by high volumes of endurance type of activity, which is a typical characteristic of military training.…”
Section: Combined Strength and Endurance Trainingmentioning
confidence: 99%
“…Similar results have also been reported in several studies using combined endurance and strength training [ 26 ], or sprint and resistance training [ 2 , 4 ]. Emergent evidence confirms that greater improvements in body composition follow resistance training in military solders [ 11 ]. Shippee et al [ 27 ] stated that, during the United States 75 th Ranger Regiment program, body mass decreased by 16%, which was reflected in the changes in body composition, whereby body fat was reduced by 10%.…”
Section: Discussionmentioning
confidence: 92%
“…Military training and operations consist of tasks that can be completed through combined strength and endurance training [ 11 ]. The analysis of the components of fitness involved in the physically demanding tasks that are carried out by rangers in battle has shown that ranger regiments have a high standard of fitness abilities and fitness programs, which are mainly focused on aerobic endurance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recruits, military training involves a high amount of physical activity, which can be a new experience for most of the recruits. Therefore, it is important to start physical training during basic training (8 weeks) and in fitness matched groups to ensure that all recruits are able to improve their physical performance in the beginning of their service and also to build a solid platform to increased physical training after the basic training period (Hofstetter, Mäder, & Wyss, 2012; Santtila, Pihlainen, Viskari, & Kyröläinen, 2015; Sporis et al, 2014). Despite technological advances and lighter material, the weight carried by a warfighter has also increased.…”
Section: Introductionmentioning
confidence: 99%